Answer:
AWWWWW :( SOOOOO SAD!!!
Step-by-step explanation:
BUT TRU UNFORINATLEY
Based on the starting temperature and the new temperature, the relevant expression would be<u> 2 - (-9) </u>
To find the number of degrees the temperature has changed by, use the following equation:
<em>= Starting temperature - Current temperature </em>
Starting temperature = 2°F
Current temperature = -9°F
The equation becomes:
<em>= 2 - (-9)</em>
In conclusion, the expression would be 2 - (-9)
<em>Find out more on </em><em>expressions </em><em>at brainly.com/question/945593. </em>